Analysis of Work Discipline And Work Facilities On Employee Performance With Work Motivation As A Mediating Variable In The Medan Belawan Primary Tax Office Medan Belawan - Combat Hamonangan Manurung; Sri Rahayu; Kiki Farida Ferine (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is a key factor in supporting the success of public organizations, including the Medan Belawan Primary Tax Office, which plays a strategic role in tax services and state revenue. This study aims to analyze the effect of work discipline and work facilities on employee performance with work motivation as a mediating variable. The study used a quantitative approach with a survey method of all 100 employees of the Medan Belawan Primary Tax Office, so the sampling technique used was a census. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The results show that work discipline has a positive and significant effect on employee performance and work motivation. Work facilities also have a positive and significant effect on employee performance and work motivation. Furthermore, work motivation has a positive and significant effect on employee performance. The indirect effect test showed that work motivation was able to mediate the effect of work discipline on employee performance, as well as mediate the effect of work facilities on employee performance. The coefficient of determination value showed that work discipline and work facilities were able to explain 35.9% of the variation in work motivation, while work discipline, work facilities, and work motivation together were able to explain 55.2% of the variation in employee performance. Based on these results, it can be concluded that improving the performance of employees at the Medan Belawan Tax Office does not only depend on the implementation of work discipline and the provision of adequate work facilities, but is also greatly influenced by the level of employee work motivation. Therefore, management is expected to strengthen disciplinary policies, improve the quality of work facilities, and create a work environment that can encourage employee motivation in order to improve performance and the quality of public services.